Validation of a heat, moisture and gas concentration transfer model for soybean (Glycine max) grains stored in plastic bags (silo bags) - Arias Barreto, Alien; Abalone, Rita Mónica; Gastón, Analía Graciela Lucia; Ochandio, Dario Carlos; Cardoso, Marcelo Leandro; Bartosik, Ricardo Enrique (2018)
A two dimensional finite element model that predicts temperature distribution and moisture content of soybean stored in silo bags due to seasonal variation of climatic conditions is described. The model includes grain respiration and calculates carbon dioxide and oxygen concentrations during storage.